2013
DOI: 10.1002/mus.23801
|View full text |Cite
|
Sign up to set email alerts
|

Muscle coactivation: A generalized or localized motor control strategy?

Abstract: Introduction We examined generalized versus joint-specific influences on muscle coactivation. Methods Muscle coactivation was assessed during maximal isometric and isokinetic knee and elbow joint extension moments in 48 healthy subjects (27 men). Local (joint-specific) and generalized (person-specific) contributions were examined using a combination of statistical tests, including regression with generalized estimating equations (GEEs), exploratory factor analysis, and cluster analysis. Results GEEs produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
1
22
0
3
Order By: Relevance
“…A secondary finding was that women had higher CMC, MHC, and LHC than men, consistent with previous studies that also found healthy women and women with KOA have greater hamstring antagonist coactivation than men . Here, we report an inverse relationship between coactivation and quadriceps strength in women but not in men.…”
Section: Discussionsupporting
confidence: 92%
“…A secondary finding was that women had higher CMC, MHC, and LHC than men, consistent with previous studies that also found healthy women and women with KOA have greater hamstring antagonist coactivation than men . Here, we report an inverse relationship between coactivation and quadriceps strength in women but not in men.…”
Section: Discussionsupporting
confidence: 92%
“…Also, coactivation was assessed during an isolated open kinetic chain strength assessment, which allowed normalization to maximal activation and was feasible in this wired sEMG study, but may not translate to coactivation strategies used during functional activities, particularly closed kinetic chain activities. Although evidence of a tendency to use coactivation as a generalized motor control strategy in open kinetic chain tasks has been demonstrated 31 , this does not rule out the possibility that coactivation during functional tasks may differ from open kinetic chain coactivation assessment.…”
Section: Discussionmentioning
confidence: 90%
“…However, there is evidence that coactivation may be modified with directed rehabilitation 30 . Additionally, muscle coactivation is, in part, a generalized motor control strategy that some individuals appear to be more prone to utilize, even when assessed using open kinetic chain strength testing 31 . This assessment of muscle coactivation during an open kinetic chain test condition is a relatively simple assay that could be assessed in clinical rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%
“…1). Although cocontraction is often used as a synonym of coactivation (Frey-Law and Avin, 2013), some authors make a distinction between these two terms. In that case, cocontraction has been defined as the deliberate concurrent activation of two antagonistic muscle groups with the purpose of stiffening a joint (Nielsen and Kagamihara, 1992).…”
Section: Coactivation Vs Cocontractionmentioning
confidence: 99%